Unobserved performance of hedge funds - Vikas Agarwal; Stefan Ruenzi; Florian Weigert (University of Cologne, Centre for Financial Research (CFR), 2020)
We investigate hedge fund firms' unobserved performance (UP), measured as the riskadjusted return difference between a fund firm's reported return and hypothetical portfolio return derived from its disclosed long equity holdings. Fund firms with high UP outperform those with low UP by 7.2% p.a. after accounting for typical hedge fund risk factors. In a horse-race, UP better forecasts fund performance than other predictors. We find that UP is positively associated with a fund firm's intraquarter trading in equity positions, derivatives usage, short selling, and confidential holdings. UP exhibits significant persistence but investors do not yet use it for manager selection.
Keywords: G11; G23; 330; Hedge fund skill; Confidential Holdings; Derivative Usage; Short Selling; Unobserved Performance